Biological resistance of thermally modified Gmelina arborea wood - Minkah, Maxidite; Afrifah, Kojo Agyapong; Antwi-Boasiako, Charles; Soares da Silva, Ana Paula; Rocha de Medeiros, Jaqueline; Paes, Juarez; Batista, Djeison; Brischke, Christian; Militz, Holger (Maderas. Ciencia y Tecnología, 2024)
Thermal modification of wood is an environmentally friendly method to improve wood durability, mainly against microorganisms. By employing a process similar to the ThermoWood®, various Gmelina arborea (gamhar) wood specimens were thermally modified at 180 °C, 200 °C, and 220 °C for 3 hours. The effects of the thermal modification process on the resistance to decay by rot-fungi, and attack by subterranean, arboreal, and dry-wood termites were determined. Generally, the thermal modification improved the resistance of Gmelina arborea (gamhar) to decay by Trametes versicolor with increasing process temperature. However, the effect of the process was null on the resistance to biodeterioration by the brown-rot fungus Coniophora puteana and the dry-wood termites Cryptotermes brevis. Even so, the visual damage caused by Cryptotermes brevis was slight. Untreated and thermally modified woods recorded higher resistance to Coniophora puteana than Trametes versicolor. Mass loss caused by Nasutitermes corniger also decreased with increasing thermal modification temperature. According to the visual damage rating values, the attack by Nasutitermes corniger was slight. However, the thermal modification inversely impacted Gmelina arborea (gamhar) attack by Macrotermes sp., as its resistance in the field to the termites decreased with increasing modification temperature. Thus, the thermal modification process contributed to improving the decay resistance of the modified wood to white-rot fungus Trametes versicolor and attack by the arboreal termites Nasutitermes corniger exposed indoors. On the other hand, thermally modified Gmelina arborea (gamhar) wood was very susceptible to Macrotermes sp. in the field. This work would provide a reliable reference document to guide wood industry stakeholders in assessing the performance of untreated and thermally modified Gmelina arborea (gamhar) wood in situations exposed to fungi and termite species adopted.